Protective and Promotive Effects of Latino Early Adolescents' Cultural Assets Against Multiple Types of Discrimination. (21st August 2017) - Cavanaugh, Alyson M.; Stein, Gabriela L.; Supple, Andrew J.; Gonzalez, Laura M.; Kiang, Lisa
Abstract : Given adversity associated with discrimination, it is important to identify culturally relevant factors that may protect against its harmful effects. Using latent variable interactions, this study examined the moderating effects of cultural assets on the association between multiple types of discrimination and adolescents' adjustment. Participants included 174 seventh‐ and eighth‐grade Latino adolescents (51% girls); majority were of Mexican origin. Peer discrimination was associated with higher internalizing symptoms, whereas cultural assets predicted higher academic motivation above and beyond racial–ethnic discrimination, demonstrating a promotive effect. Adolescents' Latino cultural assets also protected against higher levels of externalizing symptoms in the context of high peer discrimination and foreigner objectification. The discussion focuses on the conceptual and applied implications of these findings.